A Variety of Bio-nanogold in the Fabrication of Lateral Flow Biosensors for the Detection of Pathogenic Bacteria - Cheng, Nan; Yang, Zhansen; Wang, Weiran; Wang, Xinxian; Xu, Wentao; Luo, Yunbo (Current Topics in Medicinal Chemistry, 2019)
Pathogenic bacteria constitute one of the most serious threats to human health. This has led to the development of technologies for the rapid detection of bacteria. Bio-nanogold-based lateral flow biosensors (LFBs) are a promising assay due to their low limit of detection, high sensitivity, good selectivity, robustness, low cost, and quick assay performance ability. The aim of this review is to provide a critical overview of the current variety of bio-nanogold LFBs and their targets, with a special focus on whole-cell and DNA detection of pathogenic bacteria. The challenges of bio-nanogold-based LFBs in improving their performance and accessibility are also comprehensively discussed.
Keywords: Lateral flow biosensor